Networked Learning and Design Based Research for welfare innovation through further education - Oestergaard, Rina; Sorensen, Elsebeth Korsgaard (Proceedings of the International Conference on Networked Learning, 2014)
This paper sets out on a reflective journey to investigate, theoretically, the potential of a marriage between Networked Learning (NL) and Design Based Research (DBR) (Barab & Squire, 2004) in a creative and innovative pedagogical practice for welfare professionals. With reference to theoretical views on Innovative Learning (IL) and Networked Learning (NL) the paper discusses how it may be possible to gain knowledge that may help and qualify the development of creative innovative and ICT based learning designs for the future. To discuss this question the authors of the paper explore the entities of a model, which integrate the above mentioned relationships in learning designs. The suggested networked model offers possibilities of innovative learning in further educations. At the same time – in parallel – the suggested networked model offers possibilities of data generation to be used for educational research. The authors of the paper indicate and exemplify how this might be done using the theoretical embroidery of the paper in the light of the model. Finally – on the basis of the methodological and theoretical optic outlined in the paper - the authors point out research questions that may help and qualify the development of innovative DBR and NL designs directed towards the future. Assuming the views outlined and promoted in this paper, the authors claim that researchers in the field as well as welfare professionals in pedagogical, social and health areas, must display creative and innovative competences. Research findings are needed that are generated, iterated and validated through their iterative use in real life settings.